2022
DOI: 10.1002/adts.202200611
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Mechanism and Optical Behaviors of Typical Volatile Organic Compounds on Pristine and Cu/Ni‐Modified C3N Monolayer: A First‐Principles Study

Abstract: In this paper, the geometric and electronic structure of four gas molecules, including CH4, CH2O, CH3Cl and C6H6, on pristine and Cu/Ni‐modified C3N monolayer are investigated by using First principles. The calculations show that the Cu/Ni‐doping can effectively strengthen the gas adsorption ability of C3N. Upon gas‐C3N configuration, the adsorption energies are CH2O (0.11 eV) > C6H6 (0.09 eV) > CH3Cl (0.08 eV) > CH4 (0.05 eV). For Cu‐C3N configuration, the adsorption energies are C6H6 (3.26 eV) > CH3Cl (3.24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…[18][19][20] Another promising method for opening the bandgap of graphene is to replace carbon with nitrogen atoms, which creates a strong covalent organic framework. [21][22][23][24][25][26][27] Recently, crystalline carbon nitride C 3 N, a new 2D hole-free graphene-like material with a honeycomb structure and identical distribution of carbon and nitrogen atoms, has been successfully synthesized on a massive scale. 20,[28][29][30][31] Experiments have shown that the on/off ratio of 2D C 3 N FET is 6.2 × 10 10 , and the electron and hole mobilities reach 992 and 6220 cm 2 V −1 s −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Another promising method for opening the bandgap of graphene is to replace carbon with nitrogen atoms, which creates a strong covalent organic framework. [21][22][23][24][25][26][27] Recently, crystalline carbon nitride C 3 N, a new 2D hole-free graphene-like material with a honeycomb structure and identical distribution of carbon and nitrogen atoms, has been successfully synthesized on a massive scale. 20,[28][29][30][31] Experiments have shown that the on/off ratio of 2D C 3 N FET is 6.2 × 10 10 , and the electron and hole mobilities reach 992 and 6220 cm 2 V −1 s −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…25 In addition, the increasing of the N-to-C ration in carbon nitrides generates novel electronic features and chemical/physical properties such as the tunable nanopore size and band gap and adjustable conductivity, which are promising for key applications. In this context, the CN-based monolayers have been extensively used in gas sensing and exhibited high sensitivity and selectivity towards toxic gas and VOCs such as C 2 N, 34–37 C 3 N, 38–41 CN, 42–44 C 3 N 2 , 45 C 7 N 6 , 46,47 C 6 N 7 , 48 g-C 3 N 4 , 49,50 and BC 6 N 51,52 monolayers, which further motivates people's enthusiasm to exploit new C x N y structures with high-performance gas sensing. In particular for the sensing of VOCs, Agrawal et al 39 has confirmed that the C 3 N monolayer has relatively high sensing performance for acetone and isopropanol detection, while Ma et al 40 has predicted that the Cu-doped C 3 N monolayer has promising potential for optical VOCs sensors.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the CN-based monolayers have been extensively used in gas sensing and exhibited high sensitivity and selectivity towards toxic gas and VOCs such as C 2 N, 34–37 C 3 N, 38–41 CN, 42–44 C 3 N 2 , 45 C 7 N 6 , 46,47 C 6 N 7 , 48 g-C 3 N 4 , 49,50 and BC 6 N 51,52 monolayers, which further motivates people's enthusiasm to exploit new C x N y structures with high-performance gas sensing. In particular for the sensing of VOCs, Agrawal et al 39 has confirmed that the C 3 N monolayer has relatively high sensing performance for acetone and isopropanol detection, while Ma et al 40 has predicted that the Cu-doped C 3 N monolayer has promising potential for optical VOCs sensors. The g-C 3 N 4 monolayer and its composites with metal and metal oxide were demonstrated to have comparatively better gas sensing performance for detecting and decontaminating VOCs (ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation